Factors influencing consumers’ purchasing behaviour towards e-grocery shopping - Lee, Kah Lai (2018)
E-grocery shopping is consumers buying groceries on retailer’s website. It exists in Malaysia since the year 1998. However, e-grocery shopping become a trend recently with the growth of internet usage. One of the categories that most likely purchase by the consumer in 2017 is including groceries product. As the increasing of internet users, it shifted the grocery shopping into online. However, total sales of grocery purchase online still low in Malaysia. There are many factors contribute to the low usage of e-grocery. The objective of this study is to investigate the consumers’ purchasing behaviour towards e-grocery shopping in Malaysia. The variables that will be examined in this study are perceived usefulness, perceived ease of use, perceived risk, social influence, attitude towards using e-grocery, behavioural intention to use e-grocery and actual usage of e-grocery. The quantitative survey has been carried out with 400 respondents who tried e-grocery shopping before. It can be concluded that perceived ease of use and social influence plays a prominent role that influences the consumers’ purchasing behaviour towards e-grocery shopping. Hence, the e-grocery system needs to be designed user-friendly in order to ease the shopping experience. Besides, the grocers should do extensive promotion and advertising since social influence plays a role.